The Role of Service Time in Shaping the Utilization of Dental and Oral Health Services at the Dental Clinic - Anya Tania Larasati; Elok Permatasari; Yuliana Mahdiyah Daat Arina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
This study addresses the absence of research analyzing patient satisfaction in relation to the utilization of dental and oral health services at Dental Clinics of Health Center in Jember, particularly based on key determinants such as provider expertise, interpersonal relationships, service time, access, and comfort. The objectives of this study were to assess patient satisfaction with the utilization of dental and oral health services and to identify the dominant determinant influencing service utilization. A cross-sectional design with purposive sampling was employed. Data were collected using a structured questionnaire and analyzed using Pearson correlation and ordinal logistic regression. The average level of patient satisfaction was categorized as very satisfied (89%), while the average level of service utilization was classified as high (85.6%). All determinants of patient satisfaction demonstrated significant relationships with service utilization (α < 0.05). Time emerged as the dominant factor influencing the utilization of dental and oral health services, with a significance value of 0.035. These findings indicate a significant relationship between patient satisfaction and the utilization of dental and oral health services at the Dental Polyclinic of the Jember Health Center, with service time identified as the most influential determinant.Keywords: patient satisfaction; utilization of dental and oral health services; health center dental clinic